2009
DOI: 10.1152/physrev.00027.2008
|View full text |Cite
|
Sign up to set email alerts
|

The Hepatic Microcirculation: Mechanistic Contributions and Therapeutic Targets in Liver Injury and Repair

Abstract: The complex functions of the liver in biosynthesis, metabolism, clearance, and host defense are tightly dependent on an adequate microcirculation. To guarantee hepatic homeostasis, this requires not only a sufficient nutritive perfusion and oxygen supply, but also a balanced vasomotor control and an appropriate cell-cell communication. Deteriorations of the hepatic homeostasis, as observed in ischemia/reperfusion, cold preservation and transplantation, septic organ failure, and hepatic resection-induced hyperp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
371
0
18

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 433 publications
(404 citation statements)
references
References 947 publications
(1,003 reference statements)
15
371
0
18
Order By: Relevance
“…The increased expression of VEGF could therefore be a response to endothelial barrier disruption or to cellular hypoxia following SOS. In fact, microcirculatory disturbances lead to insufficient energy supply and reduced hepatic tissue oxygenation (46). The increased HIF1a mRNA levels that we detected underline the presence of hepatic hypoxia in SOS and could contribute to VEGF induction.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The increased expression of VEGF could therefore be a response to endothelial barrier disruption or to cellular hypoxia following SOS. In fact, microcirculatory disturbances lead to insufficient energy supply and reduced hepatic tissue oxygenation (46). The increased HIF1a mRNA levels that we detected underline the presence of hepatic hypoxia in SOS and could contribute to VEGF induction.…”
Section: Discussionmentioning
confidence: 61%
“…Hepatic VEGF mRNA expression is significantly increased in the rat model in parallel with sinusoidal damage (44) and serum VEGF increase correlates with the development of SOS in patients after hematopoietic stem cell transplantation (45). VEGF plays a major role in maintaining SEC differentiation (46)(47)(48). The increased expression of VEGF could therefore be a response to endothelial barrier disruption or to cellular hypoxia following SOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trophozoites of 10-50 µm in diameter with highly versatile morphology cause hindrance in sinusoids (diameter of 5-7 µm; [36]) particularly narrow and tortuous in periportal regions [15]. Obstruction may be reinforced by the recruitment of activated immune cells during the acute inflammatory response [29]. Amoebae may thus exert mechanical forces on the endothelium and the underlying Disse's space and reduce the blood flow, and consequently [7].…”
Section: Resultsmentioning
confidence: 99%
“…We observed that E. histolytica induced retraction, apoptosis and death of the human cells. LSEC retraction was detected earlier than cell death suggesting that reduced spreading of LSEC could account in vivo for the physical changes in tissue architecture allowing E. histolytica to pass the endothelial barrier and to penetrate into the liver parenchyma, a process possibly facilitated by the absence of tight junctions and by inflammation-induced gap formation between neighbouring cells [29]. In the presence of virulent amoebae, the LSEC network of actin stress fibers was disrupted, and the subcellular localisation of paxillin and phosphorylated focal adhesion kinase (FAK), key components of focal adhesion complexes formed upon activation of integrin receptors, was altered.…”
Section: Interaction Between E Histolytica and Human Liver Sinusoidamentioning
confidence: 99%